Digital Transformation of Faculty Development: Responding and Supporting Academia During Disruptions Caused by the Coronavirus Disease 2019 Pandemic. Issue 3 (9th August 2022) - Yilmaz, Yusuf; McDonald, Peter J.; Locke, Shawn; Lal, Sarrah; Bayer, Ilana; Tong, Xiao Catherine; Kundi, Anjali; Chan, Teresa M.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Introduction: The coronavirus disease 2019 pandemic disrupted the current practices for teaching and learning in medical and health professions education, creating challenges and opportunities for rapid transition. The authors describe how McMaster University's Program for Faculty Development (MacPFD) responded to this disruption by engaging in a digital transformation. Methods: The digital transformation process of MacPFD was mapped to the conceptual framework of digital transformation: Vial's building blocks of the framework. A new website was launched to host and disseminate the content. Subsequently, both the website and the content were promoted using social media tools. Content generation, Google Analytics, event registrations, and Zoom webinar attendance records were data sources for the results. Analysis of the data was based on the reach component of the RE-AIM framework. Results: Six-month data range results were reported as producer-centered and user-centered outcomes. The former consisted of 54 resources from diverse content authors, whereas the latter received 33, 045 page views from 26, 031 unique users from 89 countries. Live webinar events had 1484 registrants, with 312 (21%) being guests from external institutions. Before the coronavirus disease 2019 disruption, MacPFD was a local program to support its faculty. Discussion: The MacPFD's digital transformation shows a clear transition to a new "glocal" approach: an expanded global reach while still tending to our local development needs of the home institution's faculty members.